Harnessing rice husks: Bioethanol production for sustainable future - Sakshi Chavan; Debasis Mitra; Anuprita Ray (Current Research in Microbial Sciences)
The investigation of biofuel production from rice husks highlights its potential as a sustainable energy source amid rising environmental concerns and the gradual loss of fossil fuel sources. Biomass-derived biofuels, notably those derived from lignocellulosic materials, such as rice husks, provide a sustainable and environmentally friendly alternative that reduces greenhouse gas emissions while improving energy security. This review explores the need to produce biofuels along with the progression of biofuel technology throughout the four generations and the specific mechanisms involved in the conversion of bioethanol from rice husks. Several important stages are essential for the production of bioethanol from rice husks, including the disruption of lignocellulosic structure known as pretreatment, hydrolysis of complex carbohydrate structures into fermentable sugars, fermentation utilizing suitable microorganisms to produce ethanol, and purification of the end product by distillation. Despite significant advances, these systems still encounter challenges in terms of their cost-effectiveness and efficiency. Pretreatment techniques generally require considerable amounts of energy; the quantity of lignin influences hydrolysis effectiveness, and the process of fermentation must be carefully adapted for higher yields. This study emphasizes the need for continuing research and advancements to eliminate these obstacles. Improvements in pretreatment technologies, enzymatic applications, and fermentation procedures are essential to enhance the efficiency and cost-effectiveness of rice husk bioethanol production. By emphasizing these areas, rice husks' potential utilization as a valuable biofuel source could assist in achieving long-term energy goals while lowering the negative environmental impact of energy generation.